Gastro-oesophageal reflux: An overview of the cost-effectiveness of pharmacotherapeutic treatment options - Gustav Schellack; J. C. Meyer; Natalie Schellack (South African Family Practice)
Gastro-oesophageal reflux disease (GORD) produces symptoms that cause great irritation to the patient. Pharmacotherapeutic management is directed at minimising these symptoms and reducing the causative factors, e.g. acid production, thereby providing relieve. Currently available agents include simple antacids and acid suppression therapy, including histamine 2-receptor antagonists, proton pump inhibitors, mucosal or cytoprotective agents, pro-motility agents. Deciding on appropriate therapy will be dependent on the diagnosis, side-effects and cost-effectiveness of the treatment.